Providing HIV testing in men who have sex with men through a gay social networking app in China: A qualitative interview study with multisectoral service providers - Zhao, Tianming; Cao, Zhaobing; Jiang, Zhen; Bulloch, Gabriella; Qiu, Yanchao; Liu, Lihua; Wang, Lijing; Li, Yingxia; Jia, Ce; Guo, Li; Wu, Zunyou (Frontiers in Public Health, 2022)
Objective We explored the feasibility of app-based HIV testing services (AHTS) among men who have sex with men (MSM) according to the perspectives of testing service providers. Methods Twenty-one current or previous AHTS providers participated in a semi-structured interview which explored the facilitators and barriers to AHTS. Ten participants originating from the Center for Disease Control and Prevention (CDC) and 11 from the non-governmental organization (NGO) in Shijiazhuang, China took part in this study. Interviews was transcribed verbatim, and the socioecological model (SEM) was applied to thematic analysis. Results Twenty-one participants from AHTS services commented on the integration of online appointment schedules into HIV testing services. AHTS was deemed a convenient and efficient method for MSM and service providers to choose their preferred location and times. Moreover, it allowed for important HIV-related information to be accessed online and targeted toward at-risk individuals. Participants thought MSM may feel unsure about personal information security being stored within a privatized app and was considered a barrier to AHTS's usability. As such, they believed establishing a government-led national online platform for AHTS would allow for greater trust from MSM, rather than a social media app. Conclusion By linking booking services to an online platform, AHTS was deemed a convenient and efficient method for HIV testing services, especially for young MSM who are familiar with smartphone applications. To improve the use of these services, AHTS apps should focus on ensuring the confidentiality of personal information and internet security to build trust between MSM and service providers.